ANALISIS AKAR MASALAH PANJANGNYA WAKTU TUNGGU PROSES ADMINISTRATIF PEMULANGAN PASIEN RAWAT INAP - Sari, Dita Prawita; Harijanto, Tatong; Susilo, Harsono (Journal Nursing Care and Biomolecular, 2017)
Introduction: One critical area in the overall patient care flow in the hospital is the process of patient discharge . The high number of bed usage in the treatment room posed a problem in terms of postponing admissions and transferring new patients to the treatment room. One of the causes of postponement of admission and transfer of patients is a very long process of discharge patients 3-4 hours for general patients and more than 4 hours for insurance patients. Method: The purpose of this research is to analyze the root of the problem on the length of waiting time of administrative process of discharging patient in Hospital "N" in Malang. The research was conducted descriptively explorative through interview, observation and document search. Result and analysis: The root problems encountered include non-optimal management systems, unequal human resource (HR) capabilities, and inadequate infrastructure. The length of waiting time for the hospitals administrative discharge process at N Hospital is due to various interrelated matters in the treatment room, pharmacy installation, and administration department. Discussion: The root of the main problem that can be identified is in terms of system, human resources, and infrastructure facilities in the three units. Comprehensive remedial strategies are needed to improve the waiting time of the hospitals discharge process at Hospital N.